Ricardian fiscal regimes in the European Union - Afonso, António (2022)
The prevalence of different fiscal regimes is important both for practical policy reasons and to assess fiscal sustainability, notably for European Union countries. The purpose of this article is to assess, with a panel data set, the empirical evidence concerning the existence of Ricardian fiscal regimes in EU-15 countries. The results give support to the Ricardian fiscal regime hypothesis throughout the sample period, and for sub-samples accounting for the dates of the Maastricht Treaty and for the setting-up of the Stability and Growth Pact. Furthermore, electoral budget cycles also seem to play a relevant role in fiscal behaviour.